Valoración socioeconómica de los servicios ecosistémicos provistos por el ecosistema de bosque seco tropical presente en el DMI LURIZA, DPTO DEL ATLÁNTICO. (2018)
The ecosystems of Tropical Dry Forest have a great importance worldwide, because they harbor a great biodiversity and are a source of transcendental ecosystem services (ES) for the well-being and survival of the human being. However, the incipient level of knowledge and research carried out with respect to this important ecosystem and all the ES that it provides has meant a reduction of its vegetal cover, since they have been affected by a series of anthropogenic activities, such as the use of wood and the expansion of areas for carrying out agricultural activities. In addition to this, currently many of the ES provided by the Tropical Dry Forest do not have a defined social and economic value; therefore, it was proposed to carry out a socio-economic assessment of the ES provided by the Tropical Dry Forest present in the Luriza Regional Integrated Management District (DMI), given that it is one of the areas maintained by one of the few fragments of this ecosystem in the country. The research was carried out based on bibliographic review, field visits in the study area and the application of surveys to the social actors involved; this in order to delimit the socio-ecological system of the DMI Luriza and the different variables that influence it, the subsequent socio-economic assessment of the ES was carried out using the Contingent Valuation Method (CVM), for which the Willingness To Pay (WTP) was calculated of the inhabitants of the Municipality of Usiacurí for the conservation of the DMI Luriza, and the Willingness to Accept (WTA) a payment by the people who live in said protected area to carry out sustainable activities there. For this, hypothetical cases were raised in both study scenarios and statistical analyzes such as binary logistic regression were applied to determine the variables that influence the response of the respondents. Finally, different strategies were designed to improve the management of the protected area. Among the results obtained, it is highlighted that the main ES identified were the regulation of air quality, the provision of water and the conservation of flora and fauna species, in turn, problems such as inadequate management of solid waste were found, the felling of the forest and the unorganized tourism. Followed, it was determined that the monthly WTP per person is $7,500 COP by 71.96% of respondents in the Municipality of Usiacurí, response influenced by variables such as the seniority of these people in the population and their interest and level of importance with respect to the conservation of the ecosystem of Tropical Dry Forest, in addition the totality of the population surveyed in the DMI Luriza counts on a positive WTA, that is to say, they are arranged to receive this payment. All this allowed us to establish a Payment for Environmental Services (PES) scheme as one of the most convenient strategies for reducing the impacts on the Tropical Dry Forest ecosystem and for the proper management of the DMI Luriza. Finally, we can highlight the great need to strengthen research on biodiversity and ES in the Colombian Caribbean and specifically in the Department of Atlántico, to invigorate and encourage research from the Academy, contribute to better decision making by of the actors involved and to preserve the Tropical Dry Forest ecosystem.